2015
DOI: 10.1128/jcm.02763-14
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of a Dual Rapid Immunodiagnostic Test for HIV and Syphilis Infection

Abstract: dNew dual tests for HIV and syphilis have been developed. Our study aimed to evaluate the laboratory performance of a dual rapid immunodiagnostic test for HIV and syphilis. Our evaluation showed high performance of this dual rapid test, which should be considered for implementation to increase screening coverage and efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…For Treponema pallidum antibody detection, the electronic reader with the default cutoff value of 10 had the best sensitivity and specificity. Our results are comparable to those of laboratory evaluations that were conducted previously with different point-of-care tests for HIV and treponemal antibody detection in sera and whole blood, which also yielded high performance values for sensitivity and specificity (1,(5)(6)(7)(11)(12)(13). In our evaluation, the sensitivity of the Chembio DPP HIV-syphilis rapid test to detect HIV antibodies was somewhat greater than its sensitivity to detect syphilis antibodies, in concurrence with several other studies (5,6,11,12,14).…”
supporting
confidence: 78%
“…For Treponema pallidum antibody detection, the electronic reader with the default cutoff value of 10 had the best sensitivity and specificity. Our results are comparable to those of laboratory evaluations that were conducted previously with different point-of-care tests for HIV and treponemal antibody detection in sera and whole blood, which also yielded high performance values for sensitivity and specificity (1,(5)(6)(7)(11)(12)(13). In our evaluation, the sensitivity of the Chembio DPP HIV-syphilis rapid test to detect HIV antibodies was somewhat greater than its sensitivity to detect syphilis antibodies, in concurrence with several other studies (5,6,11,12,14).…”
supporting
confidence: 78%
“…Now, with the advent of point-of-care NAATs, the specificity and sensitivity of CT and NG tests are much higher and may be cost-effective to use in resource-limited countries. 24 As a testament to the success that can be had with STI screening, point-of-care rapid syphilis tests are now being integrated into antenatal care around the world, and some countries have even started to use a dual syphilis-HIV test, which has shown excellent performance. 25 Our study found that most of the syphilis testing was done with point-of-care tests, whereas none of the other STI tests were point of care.…”
Section: Discussionmentioning
confidence: 99%
“…192123 Additionally, a field evaluation of a dual HIV and syphilis test used in this cost-effectiveness analysis displayed excellent HIV antibody detection and very good treponemal antibody detection. 20 Those performance results are similar to evaluations of single rapid tests.…”
Section: Discussionmentioning
confidence: 90%